A Correlation Between Pregnant Women's Attitudes And Delivery Preparation With The Use Of The Maternal And Child Health (MCH) Handbook At Pmb Loly In Bengkulu City In 2025 - Stela Pramesti; Febra Ayudiah; Kintan Anissa (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The use of the Maternal and Child Health (MCH) Handbook is expected to improve the quality of maternal and child health services and nutrition, thereby achieving one of the national health development goals of reducing maternal and infant mortality rates (MMR) and infant mortality rates (IMR). The Maternal and Child Health (MCH) Handbook is disseminated through BPM), Health Center (Puskesmas), Hospitals, and Integrated Health Posts (Posyandu) (Hasanah & Susanti, 2023). Another function of the Maternal and Child Health (MCH) Handbook is as a medical record, accurately recording various issues during pregnancy, immunizations, and nutritional status, and can be used as a monitoring tool leading up to delivery (Ambarita et al., 2022). This study aims to determine the correlation between pregnant women's attitudes and childbirth preparation and the use of the MCH Handbook at PMB Loly, Bengkulu City. This study used a quantitative research method with a cross-sectional design. The population was 57 pregnant women in their third trimester who underwent prenatal care at PMB Loly. The sample was drawn using a total sampling technique. Data analysis was performed using the Chi-square test. The results of this study indicate that the majority of 41 (79.9%) pregnant women had a positive attitude towards utilizing the MCH Handbook. Most of the 32 pregnant women (56.1%) were prepared for childbirth, and most of the 33 pregnant women (57.9%) utilized the MCH Handbook in the high category. The results of the bivariate analysis using chi-squared showed a p-value of 0.000 (p < 0.05), indicating a significant correlation between childbirth preparation and the MCH Handbook utilization. This study indicates that the more positive the pregnant women's attitudes, the better their utilization of the MCH Handbook and their childbirth preparation. The bivariate analysis demonstrated a significant relationship between pregnant women's attitudes and childbirth preparation and the utilization of the MCH Handbook. It is expected that pregnant women can increase their awareness and positive attitudes towards the importance of preparing for childbirth early, one way of which is through optimal utilization of the MCH Handbook.